1995
DOI: 10.1128/jb.177.9.2276-2282.1995
|View full text |Cite
|
Sign up to set email alerts
|

Single amino acid changes in domain II of Bacillus thuringiensis CryIAb delta-endotoxin affect irreversible binding to Manduca sexta midgut membrane vesicles

Abstract: Deletion of amino acid residues 370 to 375 (D2) and single alanine substitutions between residues 371 and 375 (FNIGI) of lepidopteran-active Bacillus thuringiensis CryIAb ␦-endotoxin were constructed by site-directed mutagenesis techniques. All mutants, except that with the I-to-A change at position 373 (I373A), produced ␦-endotoxin as CryIAb and were stable upon activation either by Manduca sexta gut enzymes or by trypsin. Mutants D2, F371A, and G374A lost most of the toxicity (400 times less) for M. sexta la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
131
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(132 citation statements)
references
References 29 publications
1
131
0
Order By: Relevance
“…2 and by earlier studies (23). We are further investigating the specific role of Phe-371 in mediating membrane insertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and by earlier studies (23). We are further investigating the specific role of Phe-371 in mediating membrane insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Uracil-containing template for Cry1Ab was obtained as described (23). Primers for site-directed mutagenesis were obtained from either Integrated DNA Technologies, Inc., or Bioneer Inc. Site-directed mutagenesis was carried out using mutagene M13 in vitro mutagenesis kit as described in the manufacturer's manual (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, plasmid patterns, protein profiles and cry2-type genes of the most toxic strains were identified. Substantial evidence indicates that B. thuringiensis from different regions produce genetically and functionally different toxins (Palma et al, 2014) and a single amino acid changes in insecticidal Cry proteins can significantly alter their toxicity (Udayasuriyan et al, 1994;Rajamohan et al, 1995). The fact that some insects develop resistance against B. thuringiensis toxins after repeated exposure (Tabashnik, 1994;Ferre et al, 1995) makes it necessary to detect and identify new B. thuringiensis strains for the management of resistant insect populations.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [33], in which residues in loop 2 of Cry1Ab toxin were replaced by alanine, showed that mutant Phe 371 Ala had reduced toxicity for M. sexta larvae. Competitions experiments revealed that this mutant had similar binding parameters as Cry1Ab, but dissociation binding experiments showed that the percentage of irreversible binding (membrane insertion) was lower.…”
Section: Discussionmentioning
confidence: 99%